Pengaruh Sertifikasi Halal terhadap Peningkatan Jumlah Penjualan Produk UMKM (Studi Kasus Kota Binjai) - Berliana Dwi Nagita Manik; Elida Elfi Barus; Abi Waqqosh (el-Jizya: Jurnal Ekonomi Islam, 2024)
This research aims to determine the effect of halal certification on increasing the number of sales of Micro, Small and Medium Enterprises products in Binjai City. This research is field research using a quantitative approach. The population is all consumers and producers of micro, small and medium enterprises. The sample was selected using random sampling with a total of 100 respondents. The method used in this research is Quantitative with Simple Linear Regression using Two Variables. The research used is field research, primary data from questionnaires and secondary data from documentation. The population in this study was 100 people and the sample was determined using the Slovin method, namely 100 samples.In this research the author used quantitative research and analyzed it with SPSS 22. Based on the research results, the t test (partial) showed that the training program had a significant effect on increasing income. The calculated t value is 7.353 < t table (7.353 > 0.1660). Based on the regression results, it can be seen that the Needs variable has a calculated t value of 1,839 with a sig of 0.069. This means t count < t table (1,839 > 1,660). The second hypothesis states that the collateral factor has no significant effect on people's interest in borrowing money from loan sharks. Based on the regression results, it can be seen that the collateral variable has a calculated t value of 6.634 with a sig of 0.000. This means t count > t table (6.634 > 1.660). all independent variables (X1 and The R2 test results show that variable X (Independent) has an influence of 31.5% on variable Y (dependent), while the remaining 68.5% is influenced by other variables